RNAi-Mediated Knockdown of Calreticulin3a Impairs Pollen Tube Growth in Petunia - Piotr Wasąg (International Journal of Molecular Sciences, 2022)
Pollen tube growth depends on several complex processes, including exo/endocytosis, cell wall biogenesis, intracellular transport, and cell signaling. Our previous results provided evidence that calreticulin (CRT)—a prominent calcium (Ca2+)-buffering molecular chaperone in the endoplasmic reticulum (ER) lumen—is involved in pollen tube formation and function. We previously cloned and characterized the CRT gene belonging to the CRT1/2 subgroup from Petunia hybrida (PhCRT1/2), and found that post-transcriptional silencing of PhCRT1/2 expression strongly impaired pollen tube growth in vitro. Here, we report cloning of a new PhCRT3a homolog; we identified the full-length cDNA sequence and described its molecular characteristics and phylogenetic relationships to other plant CRT3 genes. Using an RNA interference (RNAi) strategy, we found that knockdown of PhCRT3a gene expression caused numerous defects in the morphology and ultrastructure of cultivated pollen tubes, including disorganization of the actin cytoskeleton and loss of cytoplasmic zonation. Elongation of siPhCRT3a pollen tubes was disrupted, and some of them ruptured. Our present data provide the first evidence that PhCRT3a expression is required for normal pollen tube growth. Thus, we discuss relationships between diverse CRT isoforms in several interdependent processes driving the apical growth of the pollen tube, including actomyosin-dependent cytoplasmic streaming, organelle positioning, vesicle trafficking, and cell wall biogenesis.